TINJAUAN HUKUM ISLAM DALAM PENERAPAN AKAD IJARAH PADA PRODUK RAHN DI CABANG PEGADAIAN SYARIAH ISTIQLAL MANADO - Faradila Hasan; Syarifuddin Syarifuddin; Moh. Muzwir R. Luntajo (IAIN Manado, 2016)
Islamic law doesnot merely regulate the ubudiyah problems, but it also deals with muamalah issues which are closely related to the operational processesof Islamic Financial Institutions (LKS). One of the LKSs is Islamic pawnshops that apply changing ijarah rate on theirRahnproducts in accordance with the loan given to customers despite the equal value of the pawned goods. This practice is not in accordance with the provisions of Sharia fatwaDSN-MUI No. 25 / DSN-MUI / III / 2002 about Rahn